What is a normal democracy? - O'Leary, Brendan (2021)
The author argues there is no such thing as a "normal democracy", and that the decision made by the European Court of Human Rights in Sejdić-Finci case does not pay enough respect to consociational democracy as one of the legitimate forms of democracy. As human rights have to be balanced against one another, they also have to be balanced against other values, including peace and stability. As the practical solution in the election of the three-person collective Presidency in Bosnia and Herzegovina, the author suggests three separate electoral colleges in the three territorial districts that would settle the tension between the politically viable power-sharing arrangements and the demand to respect human rights. The author concludes that more moral modesty is in place when foreign political advice in democratic constitutional design is issued for the divided societies.
Autor tvrdi da ne postoji tako nešto poput "normalne demokracije" te da odluka Europskog suda za ljudska prava u slučaju Sejdić-Finci ne uvažava dovoljno konsocijacijsku demokraciju kao jedan od legitimnih oblika demokracije. Kao što se ljudska prava moraju uravnotežiti jedna s drugima, tako se moraju uravnotežiti i s drugim vrijednostima, uključujući mir i stabilnost. Kao praktično rješenje u izborima tročlanoga kolektivnog predsjedništva u Bosni i Hercegovini, autor predlaže tri odvojena izbornička kolegija u trima teritorijalnim okruzima, što bi riješilo napetost između politički održivih aranžmana za podjelu vlasti i zahtjeva za poštivanjem ljudskih prava. Autor zaključuje kako je potrebno više moralne skromnosti kada se podijeljenim društvima daju inozemni politički savjeti o demokratskom ustavnom dizajnu.
International conference The Legacy of Peace - 25 Years of the Dayton-Paris Peace Agreement, Zagreb, 15. 12. 2020.
Abstract ; Sažetak.
Keywords: Konsocijacijska demokracija -- Ljudska prava -- Kolektivno predsjedništvo; BiH